Erikas Geschichte - Vander Zee, Ruth,Innocenti, Roberto,Haefs, Gabriele (Gerstenberg, 2013)
A woman recalls how she was thrown from a train headed for a Nazi death camp in 1944, raised by someone who risked her own life to save the baby's, and finally found some peace through her own family.
Erstausg. bei Sauerländer, 2003, ersch.
Keywords: Bilderbuch; Kind; Weltkrieg (1939-1945); Holocaust survivors; Jewish children in the Holocaust; World War; 1939-1945; Flucht; Judenvernichtung; Mädchen